PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X MA MUHAMMADIYAH BERBASIS TEKNOLOGI INFORMATIKA (MAM BerTI) PEKANBARU - ', Helmawati; ', Zulkarnain; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and improve the student’s mathematic achievement through the implementation of cooperative learning model of numbered heads together. The research is the Classroom Action Research with two cycles. The research was conducted in studentof grade X MA Muhammadiyah BerTI Pekanbaru in the even semester of the 2015/2016 academic year with the subject of as many as 22 students. The research instrument are consists of learning devices and instrument data collectors. Learning device are consists of the Syllabus, Lesson plan and Student work sheet. The instrument data collector consists of the observation sheet and math test. Technique of data analysis is analysis of narrative descriptive and analysis of statistical descriptive. The result of the research show that the learning process has improved and the student’s mathematic achievement has improved after applying the cooperative learning model of numbered heads together. The learning result in the first cycle found that the percentage of student who achieve KKM is 59,1 and the second cycle was 77,3% which increased the percentage of prior actions that only 45,5%. Therefore, The cooperative learning model of numbered heads together can be used as an alternative in learning. Key Words: Numbered Heads Together, Cooperative Learning, students learning mathematic outcomes